Trafficking of the phosphoprotein PfCRT to the digestive vacuolar membrane in Plasmodium falciparum - Kuhn, Yvonne; Sanchez, Cecilia P.; Ayoub, Daniel; Saridaki, Theodora; Van Dorsselaer, Alain; Lanzer, Michael (Traffic, 2010)
The digestive vacuole plays an important role in the pathophysiology of the human malaria parasite Plasmodium falciparum. It is a terminal degradation organelle involved in the proteolysis of the host erythrocyte's haemoglobin; it is the site of action of several antimalarial drugs and its membrane harbours transporters implicated in drug resistance. How the digestive vacuole recruits residential proteins is largely unknown. Here, we have investigated the mechanism underpinning trafficking of the chloroquine resistance transporter, PfCRT, to the digestive vacuolar membrane. Nested deletion analysis and site-directed mutagenesis identified threonine 416 as a functional residue for sorting PfCRT to its site of residence. Mass spectroscopy demonstrated that threonine 416 can be phosphorylated. Further phosphorylation was detected at serine 411. Our data establish PfCRT as a phosphoprotein and suggest that phosphorylation of threonine 416 is a possible deciding signal for the sorting of PfCRT to the digestive vacuolar membrane.
Gesehen am 08.03.2023